Determinants of vascular structure and function in at-risk children born to mothers managed for pre-eclampsia (FINNCARE study) - Renlund, Michelle; Jääskeläinen, Tiina; Kivelä, Anni; Heinonen, Seppo; Laivuori, Hannele; Sarkola, Taisto (Frontiers in Cardiovascular Medicine, 2023)
Background and aim Pre-eclampsia (PE) is related to elevated blood pressure (BP) in children. The study aims to investigate if elevated BP is reflected in child arterial health and how anthropometrics, body composition, and gestational and perinatal factors influenced this. Methods In this prospective cohort study, we assessed the arteries of 182 children exposed (46 had an early onset, with a diagnosis before 34 gestational weeks, and 136 had a late onset) and 85 children unexposed (non-PE) to PE at 8–12 years from delivery using ultra-high-frequency ultrasound in addition to ambulatory and central BPs, body composition and anthropometrics, and tonometry-derived pulse wave velocity (PWV). Results No differences were found in intima-media thickness (IMT), adventitia thickness (AT), lumen diameter (LD), local carotid artery stiffness, distensibility, or wall stress between PE-exposed and non-PE-exposed children. All children's brachial, radial, and femoral artery IMTs were associated with 24-h systolic BP (SBP) and pulse pressure, carotid–femoral PWV, and anthropometric measures. The 24-h SBP and anthropometrics, notably lean body mass, were independent predictors of peripheral artery IMTs (brachial R2 = 0.217, radial R2 = 0.208, femoral R2 = 0.214; p < 0.001). Head circumference predicted carotid artery IMT and LD (β = 0.163, p = 0.009; β = 0.417, p < 0.001, respectively), but carotid artery IMT was not associated with BP. No independent associations were found for peripheral artery ATs. Local carotid artery stiffness, distensibility, and wall stress were independently associated with adiposity. No significant associations were found between gestational or perinatal factors and child vascular health parameters. Conclusions The peripheral artery IMT of PE-exposed children is identical to that of non-PE-exposed children, but associated with BP. Adiposity is related to local carotid artery stiffness. These adverse associations in arterial health may reflect the early progression of cardiovascular disease in PE-exposed children.